Ethosomal Gel Formulation of Alpha Phellandrene for the Transdermal Delivery in Gout - Valsalan Soba, Sony (Adv Pharm Bull, 2021)
Purpose: Purpose was to improve the skin compatibility and permeability of alpha phellandrene through an ethosomal gel formulation for the treatment of gout; as the oral use of the drug is reported to cause gastrointestinal disturbances and toxicities. Methods: Alpha phellandrene loaded ethosomal formulation (APES) was prepared by cold method for the treatment of gout. APES were loaded into carbopol gel (APEG) by dispersion method. Physico-chemical characterizations of the APES were done by dynamic light scattering (DLS), transmission electron microscopy (TEM), Fourier-transform infrared spectroscopy (FTIR) etc. In vitro release, permeation, haemo-compatibility and anti-inflammatory studies were conducted. Results: APES showed a particle size of 364.83 ± 45.84 nm. The entrapment efficiency of the optimized formulation is found as 95.06 ± 2.51%. Hemolysis data indicated that APES does not cause any significant hemolysis. In vitro drug release studies were carried out using dialysis membrane technique and the amount of drug released from APES & APEG is found to be 95% and 94.21% respectively after 5 and6 hours. Kinetic data analysis revealed that APES & APEG follows first order and zero order release kinetics, respectively. The anti-inflammatory activity studies of the formulation are done by estimating its inhibitory effects on cyclooxygenase II (COX) II, lipoxygenase-5 (LOX-5), Myeloperoxidase (MPO), Inducible nitric oxide synthase (INOS) & cellular nitrite level using RAW 264.7 cells. The significant inhibition in the activities of the enzymes implies the anti-inflammatory activity of the formulations. Skin permeation study was carried out using porcine skin and revealed that the permeation of alpha phellandrene is increased from APES & APEG when compared with alpha-phellandrene solution (APS). Skin deposition study of APS, APES & APEG revealed better drug deposition from APEG (48.799 ± 1.547µg/cm(2) ) after 24 hours when compared with APS & APES. Conclusion: Overall results indicate that the ethosomal formulation of alpha phellandrene through transdermal route is an effective alternative for oral use of the drug.